Enhancing Moral Awareness for Racial Unity Through Islamic and Asian Civilization Course (TITAS): An Empirical Research from Non-Muslim Students’ Perspective - Selamat, Abu Zarrin; Hanafi, Hafizul Fahri; Salleh, Sakinah; Bahari, Aireen Aina; Hanapi, Mazarul Hasan Mohamad; Huda, Miftachul (SCAD Independent, 2020)
This article attempted to investigate the significance of the Islamic and Asian Civilization Course (TITAS) according to the point of view of non-Muslim students to form a harmonious view towards Islam besides forming and cultivating racial unity in Malaysia. This study was also conducted with expectations that TITAS will be the impetus to create moral awareness amongst non-Muslim students towards Islam and Muslims other than giving ideas that multiracial is assimilable through TITAS. This matter was aligned with the objective of the Islamic Civilization study for non-Muslim students and the goals of TITAS introduced in 1983. This study was conducted using a quantitative approach involving 203 non-Muslim students from Universiti Pendidikan Sultan Idris as the study sample. The mean was 3.81 which depicts a high-level achievement of the goals and objectives of TITAS. This showed that TITAS was able and managed to predispose moral awareness amongst non-Muslim students towards Islam and Muslims. It is also proposed that TITAS continues to be maintained as the mainstream syllabus beyond the pre-university level.